ON THE PROPERTIES OF THE PRINCIPLES OF ADMINISTRATIVE LAW - Hryshyna, Nataliia (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2025)
The effectiveness of public administration and the protection of human rights directly depends on the fundamental ideas of legal understanding embedded in society. The principles of administrative law form the universal dimension of law, symbolizing the spirit of law, which is the basis of the legal system. In view of this, the doctrinal approach to the analysis of the European administrative-legal doctrine, as well as the interpretation of the principles of European administrative law, is an extremely important scientific problem that requires further research and development by domestic lawyers. An organic component of the modern European integration course of Ukraine is the process of harmonizing national legislation with the legal system of the European Union, within which the adaptation of the norms and principles of administrative law acquires special importance. Such adaptation involves not only the formal approximation of regulatory legal acts, but also, more deeply, the perception of the legal standards of the functioning of public administration that have developed within the administrative space of the EU. An important normative and doctrinal reference point in this direction is the Concept of Administrative Reform in Ukraine, in which, even at the stage of its development, a target was declared for the gradual creation of such a system of public administration that would ensure Ukraine’s gradual entry into the circle of highly developed, legal, democratic states of the European type. This document clearly traces the influence of European principles of executive power organization, developed by the practice of the European Union, as well as scientific thought in the field of European administrative law.